PH-Dependent disruption of giant polymer vesicles: a step towards biomimetic membranes. Issue 4 (21st December 2022) - Sincari, Vladimir; Jäger, Eliézer; Loureiro, Kahynna Cavalcante; Vragovic, Martina; Hofmann, Eddie; Schlenk, Mathias; Filipová, Marcela; Rydvalová, Eliška; Štěpánek, Petr; Hrubý, Martin; Förster, Stephan; Jäger, Alessandro
Abstract : The spatiotemporal pH-triggered controlled release of a hydrophilic probe in a pH-responsive PGUV system demonstrates its potential as a biomimetic system for drug delivery, microreactors and artificial cell mimics. Abstract : Giant unilamellar polymer vesicles (GUPVs) capable of selectively delivering protected payloads into intracellular environments and releasing them in stimuli-triggered, precise spatially and temporally controlled manners are attractive bioactive cargo delivery tools. Herein, we present highly size-defined and monodisperse (42.1 ± 1.2, 60.5 ± 1.0, 80.4 ± 1.4 and 97.9 ± 1.2 μm in diameter, respectively) pH-responsive giant GUPVs prepared via microfluidic droplet generation using a flow-focusing poly(dimethylsiloxane) (PDMS)-based microfluidic device. Poly(ethylene oxide)- block -poly[2-(diisopropylamino)ethyl methacrylate] (PEO- b -PDPA) is a pH-responsive polymer that was synthesized via reversible addition–fragmentation chain-transfer (RAFT) polymerization and used in combination with poly(ethylene oxide)- block -poly(1, 2-butadiene) (PEO- b -PBD) to produce homogeneous pH-responsive giant GUPVs. To demonstrate the spatiotemporal control provided by this approach, we studied in detail the pH-responsiveness of GUPVs according to the disruption and release of dye cargo under distinct acidic conditions using fluorescence confocal microscopy. This approach can be utilized to fabricate pH-responsive delivery systems for various active compounds, microreactors, and artificial organelles, thereby paving the way towards cell mimicry.